Clinical Characteristics and Predictors of Depression among the Older Adults Attending the Family Medicine Clinic of Usmanu Danfodiyo University Teaching Hospital Sokoto in Northwestern Nigeria - Akogwu, H S; Baamlong, N D; Grema, B A; Adebisi, A S; Kaoje, A A; Abubakar, A (West African journal of medicine, 2025)
Depression represents a major international public health problem for both developed and developing countries. It is associated with increased risk of morbidity, suicide, decreased physical, cognitive and social function, and greater self-neglect, which in turn is associated with increased mortality. The study objective was to determine the clinical characteristics and predictors of depression among the elderly attending the family medicine clinic of Usmanu Danfodiyo University Teaching Hospital, Sokoto, Northwestern Nigeria. The study was a hospital-based cross-sectional study of 391 elderly participants in the family medicine clinic of Usmanu Danfodiyo University Teaching Hospital, recruited through systematic sampling technique. Data was collected using a pre-tested, structured interviewer-administered questionnaire, and Folstein (MMSE). The GDS-30 was used to screen for depression. BMI was calculated and data analyzed using SPSS version 20. Test of associations was done using the Chi-square test, and logistic regression was done; P < 0.05 was considered statistically significant. The prevalence of depression among the elderly was found to be 41.2%. Following logistic regression, being married (OR=0.559, 95% CI=0.321-0.974), bereavement in the last six months (OR=2.35, 95% CI=1.138- 4.480), poor subjective health status (OR=0.141, 95% CI=0.057-0.348), and abnormal BMI (OR=0.425, 95% CI=0.221-0.818) were found to be predictors of elderly depression in the study. The prevalence of depression among older adults was high, and the study recommends early screening, detection and management of risk factors of depressive disorder in older adults by primary care physicians.